2009
DOI: 10.3892/ijmm_00000243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of ginsenoside Rp1-mediated growth arrest and apoptosis

Abstract: Abstract. Ginsenoside Rp1, a semi-synthesized ginseng saponin, was shown to have chemopreventive action and antimetastatic potential. However, the molecular mechanisms of Rp1 on cell growth and death are not fully understood. In this study, the antiproliferative effect of Rp1 on HeLa cells in vitro was investigated. Treatment with Rp1 at 40 μM inhibited the proliferation and partial accumulation of cells at the G1 phase. Rp1-mediated G1 arrest was accompanied by decreased expression of cyclin D1, E, and A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, our group developed a novel semi‐synthetic derivative known as ginsenoside‐Rp1 (3‐O‐β‐ d ‐glucopyranosyl‐(1→2)‐β‐ d ‐glucopyranosyl dammarane‐3β,12β‐diol) by means of a reduction with hydrogenation. We previously reported that ginsenoside‐Rp1, derived from gingenoside‐Rg3 or its derivatives (2H‐Rg3, Rg5 and Rk1), exhibited improved stability and potency with strong anti‐metastatic and anti‐inflammatory activities (Kumar et al ., 2006; 2009; Park et al ., 2008; Kim and Cho, 2009); however, the anti‐platelet effect of G‐Rp1 was not then investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group developed a novel semi‐synthetic derivative known as ginsenoside‐Rp1 (3‐O‐β‐ d ‐glucopyranosyl‐(1→2)‐β‐ d ‐glucopyranosyl dammarane‐3β,12β‐diol) by means of a reduction with hydrogenation. We previously reported that ginsenoside‐Rp1, derived from gingenoside‐Rg3 or its derivatives (2H‐Rg3, Rg5 and Rk1), exhibited improved stability and potency with strong anti‐metastatic and anti‐inflammatory activities (Kumar et al ., 2006; 2009; Park et al ., 2008; Kim and Cho, 2009); however, the anti‐platelet effect of G‐Rp1 was not then investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Rg3, 2H‐Rg3, G‐Rg5 and Rk1) by means of a reduction with hydrogenation and was verified to be chemically stable (Park and Park, 2005). In addition, G‐Rp1 displayed 10‐fold more potent anti‐cancer activity compared with G‐Rg3 and G‐Rg5 (Park et al ., 2008; Kumar et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%